Analisis Citra Koperasi Dalam Upaya Meningkatkan Minat Masyarakat Untuk Berkoperasi - Shofwan Azhar Solihin; Ahmad Sugih Mukti; Ucu Nurwati (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
Geographically Subang Regency has a very complete earth surface starting from the mountain highlands to the coastal and sea lowlands with multi-ethnic and ethnic populations as well as uneven levels of education and the interests of the Subang people who tend to migrate to work and build areas outside Subang Regency, as for the industries and even the agricultural and service sectors are mostly filled by workers from outside the Subang area. The distribution of cooperatives in Subang Regency has not been evenly distributed due to various challenges, around 80% of the cooperatives were not able to hold an annual member meeting (RAT) and have not been able to provide excellent service for members and non-members so that the ability to manage cooperatives has not been maximized. The purpose of this research is to find out the influence of the image of cooperatives in increasing public interest in cooperatives in Subang Regency. The research method used in this research is a descriptive analytic method with a case study approach to obtain in-depth data and information. The instrument used in this study was distributing questionnaires to the general public, students and civil servants as respondents. Based on the research result, it is known that members' responses regarding the role of cooperative image have a positive relationship to interest in cooperatives, but there are still some things with less criteria and need improvement in several aspects. In this study, there will be several efforts that must be made to increase the community's interest in cooperatives in Subang Regency, West Java Province.